2018
DOI: 10.18203/2349-2902.isj20180338
|View full text |Cite
|
Sign up to set email alerts
|

Cervical spondylosis: analysis of clinical and radiological correlation

Abstract: Background: Cervical spondylosis is a chronic degenerative lesion of the cervical intervertebral discs causing axial neck pain, cervical radiculopathy and myelopathy. This study was undertaken to study the clinical and radiological correlation in cervical spondylosis with respect to clinical and radiological findings.Methods: A prospective observational study was done on 100 patients with cervical spondylosis treated in a tertiary care centre of South Kerala. The sociodemographic details, clinical and radiolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…Most of the participants with either cervical or lumbar spine pathologies in this study were males. This finding is in harmony with the findings of the studies conducted by Dallbayrak et al [9] ; Harkema et al [10] ; Laxton and Perrin [11] , Maaji et al [12] ; Motter et al [13] ; Mustapha et al [5] , Olarinye-Akorede et al [6] ; RoseBist et al [14] , Ogolodom et al [15] , which also reported more males than their female counterparts.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Most of the participants with either cervical or lumbar spine pathologies in this study were males. This finding is in harmony with the findings of the studies conducted by Dallbayrak et al [9] ; Harkema et al [10] ; Laxton and Perrin [11] , Maaji et al [12] ; Motter et al [13] ; Mustapha et al [5] , Olarinye-Akorede et al [6] ; RoseBist et al [14] , Ogolodom et al [15] , which also reported more males than their female counterparts.…”
Section: Discussionsupporting
confidence: 86%
“…Among those with cervical spine pathologies, the least had Nurick grade IV, in which they were able to walk with the aid of someone or frame. This finding is in consonance with the finding of the study carried out by Ogolodom et al [15] , but not in agreement with the findings of the studies conducted by Olarinye-Akorede et al [6] and RoseBist et al [14] . Nurick grades III and IV scores were reported in the study conducted by Olarinye-Akorede [6] .…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation